A rare case of gint lipomatous hypertrophy of the atrial septum - Carino, Davide; Agostinelli, Andrea; Ricci, Matteo; Romano, Giorgio; Nicolini, Francesco; Gherli, Tiziano (Acta Biomedica Atenei Parmensis, 2018)
Benign lipomatous lesion of the heart includes  an heterogeneous group of entities including neoplastic, congenital and reparative phenomena. Among these lipomas and lipomatous hypertrophy of the atrial septum ( LHIS) represent the most common lesion. Patients suffering from LHIS are often asymptomatic, however atrial fibrillation, congestive heart failure and supraventricular tachycardia are typical findings. Here we present a rare case of LHIS symptomatic  for asthenia and dyspnea.